Mechanisms of cooperation between airlines and online travel agencies for flight crowdfunding. (26th February 2022) - Ling, Liuyi; Bao, Xuefeng; Zhang, Zihao; Yang, Feng
Abstract: With the development of crowdfunding and e‐commerce, a novel selling strategy for airlines called flight crowdfunding has been recently applied to the airline industry. In this paper, we propose a micro‐foundation to analyze consumers' purchase behavior, the interaction between airlines and OTAs for launching crowdfunding flights and design contracts to coordinate the supply chain. We find that airlines tend to reduce the participation threshold below the break‐even point to attract more consumers, even if doing so will incur losses when the demand is insufficient. We also examine the conditions under which crowdfunding dominates the traditional selling and find that airlines will adopt crowdfunding as the selling strategy if the competition is sufficiently intense in the market or flights' fixed cost is sufficiently high. Moreover, all consumers always strictly benefit from the crowdfunding offer. Crowdfunding can create a win–win–win situation for airlines, the OTA and consumers if the number of airlines in the market is in an intermediate range. We also investigate the supply chain coordination contracts and demonstrate that cost‐sharing contracts can coordinate the supply chain and achieve its optimal performance, whereas some other contracts, such as wholesale‐price, revenue‐sharing, and profit‐sharing contracts cannot do that. This paper highlights the importance of crowdfunding in the cooperation between airlines and OTAs.